Estrogen-mediated downregulation of HIF-1 alpha signaling in B lymphocytes influences postmenopausal bone loss - Meng, Xianyi; Lin, Zhen; Cao, Shan; Janowska, Iga; Sonomoto, Koshiro; Andreev, Darja; Knab, Katharina; Wen, Jinming; Knaup, Karl; Krönke, Gerhard; Rizzi, Marta; Schett, Georg; et al. (Bone Research, 2022)
In the bone marrow, B cells and bone-resorbing osteoclasts colocalize and form a specific microenvironment. How B cells functionally influence osteoclasts and bone architecture is poorly understood. Using genetically modified mice and high-throughput analyses, we demonstrate that prolonged HIF-1 alpha signaling in B cells leads to enhanced RANKL production and osteoclast formation. In addition, deletion of HIF-1 alpha in B cells prevents estrogen deficiency-induced bone loss in mice. Mechanistically, estrogen controls HIF-1 alpha protein stabilization through HSP70-mediated degradation in bone marrow B cells. The stabilization of HIF-1 alpha protein in HSP70-deficient bone marrow B cells promotes RANKL production and osteoclastogenesis. Induction of HSP70 expression by geranylgeranylacetone (GGA) administration alleviates ovariectomy-induced osteoporosis. Moreover, RANKL gene expression has a positive correlation with HIF1A expression in human B cells. In conclusion, HIF-1 alpha signaling in B cells is crucial for the control of osteoclastogenesis, and the HSP70/HIF-1 alpha axis may serve as a new therapeutic target for osteoporosis.
CRIS-Team WoS Importer:2022-03-04

Protektive Makrophagen: Neue Einblicke zur Rolle von Synovialmakrophagen bei entzündlichen Gelenkerkrankungen - Knab, Katharina; Chambers, David; Krönke, Gerhard (Zeitschrift für Rheumatologie, 2021)
Macrophages are among the phylogenetically oldest cells of the immune system and are found in all tissues and organs. In addition to playing an important role in immune response against pathogenic microorganisms, these cells were previously described to play a vital role in chronic inflammatory diseases such as rheumatoid arthritis. Using novel techniques such as single-cell sequencing and advanced microscopy techniques it has now been shown that macrophages are far more versatile. Thus, these cells contribute considerably to tissue homeostasis and tissue regeneration. As each tissue has to fulfill special requirements, macrophages vary in their phenotype and function between organs. New data have now identified a specialised population of epithelioid macrophages that exert a protective and anti-inflammatory function in synovial tissue and prevent the initial onset as well as episodes of joint inflammation in rheumatoid arthritis.
CRIS-Team Scopus Importer:2021-11-05
Keywords: Macrophage heterogeneity; Macrophage ontogeny; Resident macrophages; Synovial macrophages; Synovial microenvironment

Repeated CXCR4 Blockade by Plerixafor Attenuates Transplant Vasculopathy in Murine Aortic Allografts - Theil, Frank; Kuckhahn, Annika; Hörning, André; Völkl, Simon; Knab, Katharina; Fritz, Niklas; Gräbner, Cindy; Ramsperger-Gleixner, Martina; Weyand, Michael; Heim, Christian (Journal of Immunology, 2024)
Plerixafor, a hematopoietic stem cell mobilization agent, increases the peripheral blood content of effector and regulatory T cells and may have beneficial effects on cardiac allograft vasculopathy. The aim of the current study was to evaluate its effects in a murine aortic allograft model using different application procedures. Allogeneic donor aorta grafts (n 5 8/group) from C57BL/6 mice(H2b) were abdominally transplanted into CBA mice (H2k). Plerixafor application was performed either continuously for 14 d using abdominally implanted osmotic pumps (1 mg/kg/d) or i.p. with a single dose (1 and 5 mg/kg) on day 0 or pulsed injections of 1 mg/kg on days 0, 7, 14, and 21. Cell distribution was monitored by FACS. Aortic grafts were evaluated for neointima development by Elastica-van-Gieson on day 30. Immunofluorescence and intragraft gene expression analysis were performed. On day 14, significantly fewer hematopoietic stem cells were found in the bone marrow of all plerixafor-treated mice. In the pulsed application group, significantly more hematopoietic stem cells were found in the peripheral blood on day 14 (0.045 ± 0.002%; p < 0.01 [pulsed]; versus 0.0068 ± 0.002% [control]) and also more regulatory T cells. PCR revealed lower inflammatory cytokines. The luminal occlusion was significantly reduced in the pulsed treated group (33.65 ± 8.84 versus 53.13 ± 12.41) going along with decreased neointimal CD4+ T cell and plasmacytoid dendritic cell infiltration, as well as less smooth muscle cell proliferation. The application of plerixafor attenuates chronic rejection in aortic allografts via immunomodulatory effects. Injection of repeated low-dose plerixafor is the most effective application form in the aortic transplant model.
CRIS-Team Scopus Importer:2024-11-22

Stunning of neutrophils accounts for the anti-inflammatory effects of clodronate liposomes - Culemann, Stephan; Knab, Katharina; Euler, Maximilien; Wegner, Anja; Garibagaoglu, Hilal; Ackermann, Jochen; Fischer, Kim; Kienhoefer, Deborah; Crainiciuc, Georgiana; Hahn, Jonas; Grüneboom, Anika; Nimmerjahn, Falk; et al. (Journal of Experimental Medicine, 2023)
The authors show that the anti-inflammatory effects of clodronate liposomes do not result from the depletion of mononuclear phagocytes but from a functional stunning of polymorphonuclear neutrophils. These findings necessitate a critical revision of the current literature on the role of monocytes and macrophages in inflammation.
CRIS-Team WoS Importer:2023-04-28

Synovial Macrophage and Fibroblast Heterogeneity in Joint Homeostasis and Inflammation - Knab, Katharina; Chambers, David; Krönke, Gerhard (Frontiers in Medicine, 2022)
The synovial tissue is an immunologically challenging environment where, under homeostatic conditions, highly specialized subsets of immune-regulatory macrophages and fibroblasts constantly prevent synovial inflammation in response to cartilage- and synovial fluid-derived danger signals that accumulate in response to mechanical stress. During inflammatory joint diseases, this immune-regulatory environment becomes perturbed and activated synovial fibroblasts and infiltrating immune cells start to contribute to synovial inflammation and joint destruction. This review summarizes our current understanding of the phenotypic and molecular characteristics of resident synovial macrophages and fibroblasts and highlights their crosstalk during joint homeostasis and joint inflammation, which is increasingly appreciated as vital to understand the molecular basis of prevalent inflammatory joint diseases such as rheumatoid arthritis.
CRIS-Team Scopus Importer:2022-09-09
Keywords: fibroblasts; inflammation; macrophages; rheumatoid arthritis; single-cell sequencing; synovial tissue